The Effects of Total Asset Turnover, Return on Assets, And Sales Growth on Financial Distress in Food and Beverage Companies over the Period 2016-2020 - Kumba Digdowiseiso; Intan Sulistia Ningrum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effects of fundamental factors, namely Total Assets Turnover (TATO), Return on Assets (ROA), and sales growth on food and beverage sector companies during the 2016-2020 period. The population of this research is the food and beverage sector companies that remain listed on the Indonesia Stock Exchange between 2016 and 2020. Sampling was carried out by purposive sampling consisting of 30 companies. By using the STATA 16 program, the research data were analyzed using a panel data regression approach with a significance level of 0.05. This analysis showed that the ROA and sales growth variables had a positive and significant effect on financial distress. Meanwhile, TATO was not significant to financial distress.